FILE SENDING VIA DIFFERENT MOBILE CHANNELS: AN OPPORTUNISTIC APPROACH - Chua, Maxwell; Aquino, Chloebelle; Santos, Jan Vincent; Festin, Cedrik Angelo M. (Philippine Engineering Journal, 2013)
Data and information transfer among mobile devices is very important in this technology-driven world. The Short Message Service (SMS), Multimedia Messaging Service (MMS), and Third Generation (3G) mobile technology are such services that allow users to relay data among mobile devices. However, these channels are faced with their own corresponding challenges and issues which affect the reliability and cost efficiency of data transfer. This paper presents implementations of applications that allow the transfer of any form of data using the three channels specified above. In addition, it introduces an opportunistic system which has the ability to incorporate all three channels, as well as to choose which one to use in sending data at any given time. However, such system is very costly in resources. It is costly in memory because it uses threads, and also in mobile credits because of its use of SMS, MMS, and 3G services. The project, nonetheless, established a reliable data transfer protocol among mobile devices by allowing each channel to compensate for one other’s disadvantages.